2016
DOI: 10.1002/jbm.a.35729
|View full text |Cite
|
Sign up to set email alerts
|

l-Glutathione enhances antioxidant capacity of hyaluronic acid and modulates expression of pro-inflammatory cytokines in human fibroblast-like synoviocytes

Abstract: Intra-articular injection of hyaluronic acid (HA) has been widely accepted for the treatment of osteoarthritis (OA) in early stage. l-Glutathione (GSH), an antioxidant, has an anti-inflammatory effect on protecting cells from reactive oxygen species and reactive nitrogen species (ROS/RNS). In this study, the therapeutic effects of HA (0.1%) supplemented with GSH (0, 5, 10, and 20% in weight ratios to HA) on human fibroblast-like synoviocytes (FLSs) were evaluated. The results showed that cell morphology and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
0
22
1
Order By: Relevance
“…However, TNF‐alpha was found to be higher in the range of 7–12% than the control group. Contrary to our results, Neuman and colleagues, and Yang and coworkers determined that HA downregulated pro‐inflammatory cytokine. In the literature, it also is suggested that low molecular weight HA stimulates pro‐inflammatory cytokines and also NOS .…”
Section: Resultscontrasting
confidence: 99%
“…However, TNF‐alpha was found to be higher in the range of 7–12% than the control group. Contrary to our results, Neuman and colleagues, and Yang and coworkers determined that HA downregulated pro‐inflammatory cytokine. In the literature, it also is suggested that low molecular weight HA stimulates pro‐inflammatory cytokines and also NOS .…”
Section: Resultscontrasting
confidence: 99%
“…[391] A systematic review, which included data from six randomized controlled trials comparing the effectiveness of PRP with other intra-articular injections, exercise, or analgesia for a minimum of 6 months PRP produced statistically significant improvements in WOMAC scores for up to 12 months. [393][394][395] www.advancedsciencenews.com www.advtherap.com HA hydrogel n/a Dexamethasone Cortocosteroid [310] Adant (Suprahyal) 500-1000 Tenoxicam NSAID [311] Variofill (Adoderm, Langenfeld, Gmbh) HMWCR Diclofenac Sodium clodronate Triamcinolone acetonide Ropivacaine HCl NSAID DMOAD Cortocosteroid Anaesthetic [312] [ 313] Hydros, Hydros-TA HMW Triamcinolone acetonide Cortocosteroid [314] Cingal 1900 Triamcinolone acetonide Cortocosteroid [315] Hylan GF-20 HMWCR Triamcinolone acetonide Cortocosteroid [316] HA solution 800 Mannitol Anti-oxidant [317] Go-on matrix Ostenil Plus 1500 Mannitol Anti-oxidant [320] Happyvix 1500 Mannitol Anti-oxidant [320] Happycross 1500 Mannitol Anti-oxidant [320] Synolis V-A 2000 Sorbitol Anti-oxidant [320] HA 4AR conjugate 2200 4 aminoresorcinol Anti-oxidant [321] Ostenil 1000-2000 l-glutathione Anti-oxidant [322] Arthrum HCS 2800 CS GAG [320] Surgical Syonium 2800 CS GAG [320] HA-sCT conjugate 200 Salmon calcitonin DMOAD [323] HA ADAMTS inhibitor n/a ADAMTS inhibitor DMOAD [324] HA hydrogel 60-120 Doxycycline DMOAD [296] Hanox Hanox M-XL 1500 n/a Cortivazol Triamcinolone hexacetonide Mannitol + lidocaine clorhydrate Cortocosteroid Cortocosteroid Anti-oxidant + local anaesthetic [325] n/a, not available; HMW, high molecular weight; HMWCR, high molecular weight cross-linked. [393][394][395] www.advancedsciencenews.com www.advtherap.com HA hydrogel n/a Dexamethasone Cortocosteroid [310] Adant (Suprahyal) 500-1000 Tenoxicam NSAID [311] Variofill (Adoderm, Langenfeld, Gmbh) HMWCR Diclofenac Sodium clodronate Triamcinolone acetonide Ropivacaine HCl NSAID DMOAD Cortocosteroid Anaesthetic …”
Section: Therapeutic Properties Of Platelet Rich Plasmamentioning
confidence: 99%
“…HA supplemented with glutathione exhibits improved antioxidant capacity and modulates proinflammatory cytokine expression in human fibroblast‐like synoviocytes. Glutathione has the potential to augment the effect of visco‐supplementation mediated by HA in patients with osteoarthritis (Yang, Wu, Chen, Sumi, & Huang, ). Amino acids are required to build dermal extracellular matrix proteins, mainly collagens, and a number of vitamins and minerals have important functions that are relevant to the skin aging process (Prikhnenko, ).…”
Section: Discussionmentioning
confidence: 99%